Dampak ukuran perusahaan, persistensi laba, alokasi pajak antar periode terhadap tax retention rate dengan pemoderasi manajemen pajak pada perusahaan manufaktur BEI 2015-2016 - Katuruni, Innas Susantira (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
It is undeniable that state revenues to date have mostly come from the tax sector which is used to support national development. However, there are many opinions that make some companies think that tax is one of the burdens that can reduce the income or profit generated. Thinking like this is what makes taxpayers do various ways to minimize their tax burden, both legally and illegally. One of the steps that can be chosen is to take several tax management steps that can be taken by the company. One of them is tax planning. In the implementation of tax planning, the company's management requires a tool that is considered accurate to make observations on the level of effectiveness of tax management, one of which is the level of tax retention (tax retention rate). The level of tax retention can be used as a tool to monitor the success of the level of corporate tax management. A company will try to minimize its tax burden as an effort to improve the quality of company profits.